Perancangan Mikrostrip Square Patch Array MIMO pada Frekuensi 60 GHz untuk Jaringan 5G WiGig - Muhammad Ridho Efendi; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
WiGig (Wireless Gigabit) is the next generation technology of WiFi (Wireless Fidelity). WiGig speeds reach 7Gbps / s and have great access. In this study, microstrip antenna Square Patch Array MIMO (Multiple Input Multiple Output) for WiGig application operating at 60 GHz is discussed. Microstrip antenna is designed by using MIMO Technique to increase the gain. Antenna is simulated by using CST(Computer Simulation Technology) Microwave Studio software. From the simulation results, the antenna can operate at a frequency of 60 GHz. The bandwidth obtained is 4.38 GHz (7.3%) on VSWR 1.06 and the gain is 14.3 dB.Keyword: WiGig, MIMO, Gain, Bandwidth, VSWR